2021
DOI: 10.3390/molecules26020335
|View full text |Cite
|
Sign up to set email alerts
|

Novel Amides Derivative with Antimicrobial Activity of Piper betle var. nigra Leaves from Indonesia

Abstract: Piper betle var. nigra is a tropical plant closely related to the common piper. P. betle has also been dubbed a promising source of natural antioxidants in herbal health products, antibacterial, antifungal, antimalarial, cytotoxic activity against the cancer cell lines K562 and HL-60, and antileishmanial. The aim of this study to observation Antimicrobial activity and isolation of chemical compound. The antimicrobial activity of P. betle extract was performed by well diffusion method against two oral pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 24 publications
1
14
0
1
Order By: Relevance
“…According to recent reports, the ethanolic extract of P. nigrum showed antifungal activity with MIC values between 500–2000 μg/mL against reference strains of C. albicans using the disc diffusion technique [ 48 ]. Our results are comparable with studies that have demonstrated the antibacterial and antifungal activity of the ethanolic extract of P. nigrum against clinically important pathogens such as E. coli, S. aureus, and C. albicans [ 70 , 71 ]. Furthermore, some studies have shown that the ethanol fraction is often the most effective [ 72 , 73 ].…”
Section: Discussionsupporting
confidence: 89%
“…According to recent reports, the ethanolic extract of P. nigrum showed antifungal activity with MIC values between 500–2000 μg/mL against reference strains of C. albicans using the disc diffusion technique [ 48 ]. Our results are comparable with studies that have demonstrated the antibacterial and antifungal activity of the ethanolic extract of P. nigrum against clinically important pathogens such as E. coli, S. aureus, and C. albicans [ 70 , 71 ]. Furthermore, some studies have shown that the ethanol fraction is often the most effective [ 72 , 73 ].…”
Section: Discussionsupporting
confidence: 89%
“…2-hexenoic acid (2) was observed as an Oil yellow, with its molecular composition established as C6H10O2, based on HR-TOFMS. This showed a [M+H]+ ion peak at m/z 115.1211 (calcd.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous study of Piper betle L. Var. nigra Two amide derivatives, piperenamide A-B have also been reported to have activity against two oral pathogenic bacteria and opportunistic pathogenic [2].…”
Section: Introductionmentioning
confidence: 99%
“…nigra is a plant used as a spice and medicine belonging to the Piperaceae family. It contains many bioactive chemicals such as cadinene, caryophyllene, and amide alkaloids [79,80], and the extract of P. betle showed inhibitory effects against C. albicans according to a disk diffusion test [81].…”
Section: Alkaloidsmentioning
confidence: 99%